Analysis of Business Development Strategy Effectiveness at Bank BJB Cimahi Branch - Restiawati, Alvi (Dinasti International Journal of Management Science, 2025)
This study aims to evaluate the effectiveness of business development strategies implemented by Bank BJB Cimahi Branch. Using a qualitative case study approach, this research analyzes the existing strategies through the SWOT, PESTLE, and Porter’s Five Forces frameworks. The findings indicate that the implemented strategies are effective in enhancing the company’s operational efficiency and competitiveness. However, there are shortcomings in the aspects of digital innovation and market penetration that require further attention. The recommendations include strengthening digital services and developing marketing strategies that are more adaptive to the needs of modern customers.